Симода: роман / Николай Задорнов - Задорнов Николай Павлович (Сибириада, 2022)
Экземпляры: ф.5 (20230413) / Инвентарный номер: 63308 / Цена: / Сис.шифр: 84(2Рос=411.2)6-4 / Авт.знак: З-15 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=411.2)6-44